Pelatihan Penerapan 5S (Sapa Salam Senyum Sopan Santun) Demi Terciptanya Lingkungan Berakhlaqul Karimah di Desa Tegalsari Nganjuk - Adeliya Agil Putri Pratiwi; Siti Kalimah (LP3M IAIFA Kediri, 2020)
The environment of karimah is an environment that should be given to children from an early age, where children are accustomed to acting politely and saying with courtesy, thus the assistance of this community is carried out and directed to provide awareness and learning through the application of 5S (Greetings Smile Politeness). This mentoring activity is indeed quite impactful in the daily habits of children when in school, but when outside school children will be faced again with an environment that does not practice karimah. So, in this mentoring period researchers also do good work and communication to the community and the participation of the community of Sukomoro Nganjuk Cotton Village actively in succeeding the program. The establishment of a moral environment cannot necessarily succeed only with the application of 5S (Sapa Salam Senyum Sopantun) conducted during the study only, so the researcher appealed to the community, especially the college staff to civilize the application of the 5S to the children of students. The success of this program can be used as a model of the implementation of moral education elsewhere by adjusting the existing context.